Utilization of Google Suite for Education (GAFE) in the IPDN Library - Hapsari, Rian Dwi (Indonesian Journal of Librarianship, 2022)
Background: GAFE is designed for the learning processes between teachers andstudents. Interestingly that GAFE is applied as a new breakthrough in improving themanagement and services at IPDN libraries. Purpose: This study aims to find out theextent of the use of GAFE in the IPDN Library. Methods: This research uses aqualitative descriptive method with 15 librarians as the subject of the research. Result:The results show that IPDN Librarians feel more effective in managing and givingservices in the library, especially in collaboration to make reports, statistical data,promotion slides, surveys, and activity planning. Moreover, it helps the library to carryout cross-campus library meetings/coordination. The most intensely used GAFEfeatures which are used almost every day by all respondents are G-Mail, Google Drive,Google Forms, and Google Meet. While the features that have a moderate level of use areGoogle Documents, Google Sheets, and Google Slide. The features that are rarely used byIPDN librarians are Google Calendar, Google Classroom, and Google Sites. Conclusion:This study concludes that GAFE features have been well utilized in IPDN Library. Keywords: Utilization of GAFE; Library Management; Library Services; Google forEducation; IPDN Library